Method for preparing anhydrous gypsum through phosphogypsum crystal transformation and purification
By using dialkali metal salts of ethylenediaminetetraacetic acid and alkali metal chlorides as crystal-transforming agents, the crystal growth of phosphogypsum was regulated, solving the problems of high energy consumption and unfavorable whisker structure in the preparation of anhydrous phosphogypsum. High-purity, high-compressive-strength columnar anhydrous gypsum was prepared, broadening its application range.
Patent Information
- Application Number
- CN202511085380.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-04
- Publication Date
- 2025-10-24
AI Technical Summary
Existing methods for preparing anhydrous gypsum from phosphogypsum suffer from high energy consumption, crystal structure collapse, and whisker structures that are not conducive to high-strength applications, especially limiting their application in the construction field.
The crystal growth process of phosphogypsum was controlled by using dialkali metal salts of ethylenediaminetetraacetic acid and alkali metal chlorides as crystallization agents. High-purity, high-compressive-strength columnar anhydrous gypsum was prepared by reacting it with a mixed solution of sulfuric acid and nitric acid under specific temperature and time conditions.
This method enables the efficient and low-energy preparation of high-purity, high-compressive-strength columnar anhydrous gypsum, broadening its application areas, especially its potential in building materials.
Smart Images

Figure CN120829261A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of industrial solid waste resource utilization, and particularly relates to a method for preparing anhydrous gypsum by phosphogypsum crystal transformation and purification. BACKGROUND
[0002] Phosphogypsum is an industrial solid waste produced in the process of wet-process phosphoric acid production, and its main component is CaSO4·2H2O. In addition, it also contains incompletely decomposed phosphate rock, quartz, and residual phosphoric acid, phosphate, fluoride, heavy metals, organic matter and other impurities. These impurities exist in different forms such as lattice doping, atomic replacement, surface adsorption and interstitial filling, which are the key to the resource utilization of phosphogypsum. At present, domestic phosphogypsum is mainly disposed in the form of stacking, which not only occupies a large amount of land resources, but also has high environmental risk. The main resource utilization methods mainly focus on the preparation of cement, soil conditioner and building materials from phosphogypsum, but the added value of these products is low.
[0003] In recent years, relevant researches have shown that anhydrous gypsum prepared from phosphogypsum has good thermal stability, chemical stability and high mechanical strength, and can be applied in the field of high polymer filling materials, which is an important way for the resource utilization and high value utilization of phosphogypsum. At present, anhydrous gypsum is mainly prepared by acidification method, hydrothermal method and calcination method. However, the calcination method needs to react at more than 600 DEG C, which has high energy consumption and is easy to cause the collapse of crystal structure, affecting the application of anhydrous gypsum in the field of materials.
[0004] The atmospheric acidification method is an effective method for preparing anhydrous gypsum by liquid phase crystal transformation of phosphogypsum due to its low energy consumption and the difficulty of crystal structure collapse. In this method, the role of the mixed solution of sulfuric acid and nitric acid is mainly to provide a dissolution environment for the dissolution of phosphogypsum. When the concentration of calcium ions and sulfate ions in the acid solution reaches the saturation concentration of anhydrous gypsum, anhydrous gypsum begins to precipitate. However, during the growth and development of anhydrous gypsum, due to the difference in crystal face energy, it tends to grow continuously in the c-axis direction, so the morphology of the product is columnar or acicular, that is, anhydrous calcium sulfate whisker. This slender whisker structure is not conducive to the subsequent utilization of anhydrous gypsum. Secondly, the strength of gypsum is related to the crystal morphology. When the crystal develops into a thick and dense short column, the compressive and flexural strengths will be greatly improved. If the aspect ratio of anhydrous calcium sulfate whisker is too large, it cannot be applied in the building field and other application scenarios which have high requirements on product strength.
[0005] Therefore, it is necessary to design an improved method for preparing anhydrous gypsum by phosphogypsum crystal transformation and purification to solve the above problems. SUMMARY
[0006] The present application relates to the technical field of industrial solid waste resource utilization, and particularly relates to a method for preparing anhydrous gypsum by phosphogypsum crystal transformation and purification.
[0007] To achieve the above-mentioned purposes, in a first aspect, the application provides a method for preparing anhydrite by phosphogypsum crystallization and purification, comprising the following steps:
[0008] S1, uniformly mixing phosphogypsum, an acid mixture, and a crystallization agent to obtain a phosphogypsum mixed solution; the acid mixture is composed of a nitric acid solution and a sulfuric acid solution;
[0009] S2, reacting the phosphogypsum mixed solution obtained in step S1 at 80-100℃ for 100-150 min, and then drying to obtain anhydrite.
[0010] Preferably, in step S1, the crystallization agent is composed of a di-alkali metal salt of ethylenediaminetetraacetic acid and an alkali metal chloride, the di-alkali metal salt of ethylenediaminetetraacetic acid is added in an amount of 0.3-0.5% of the dry basis mass of phosphogypsum, and the alkali metal chloride is added in an amount of 0-15% of the dry basis mass of phosphogypsum.
[0011] Preferably, the di-alkali metal salt of ethylenediaminetetraacetic acid is disodium ethylenediaminetetraacetate and / or dipotassium ethylenediaminetetraacetate, and the alkali metal chloride is potassium chloride and / or sodium chloride.
[0012] Preferably, in step S1, the ratio of the dry basis mass of phosphogypsum, the volume of the acid mixture, and the mass of the crystallization agent is (0.8-1.2):(4.7-5.3):(1.6-2.2).
[0013] Preferably, in step S1, the mass fraction of the nitric acid solution is 30-40%, the mass fraction of the sulfuric acid solution is 10-20%, and the volume ratio of the sulfuric acid solution to the nitric acid solution is (1-1.5):(2-2.6).
[0014] Preferably, in step S2, the drying temperature is 60-70℃, and the drying time is 10-14 h.
[0015] In a second aspect, the application provides anhydrite, wherein the aspect ratio of the anhydrite is 0.9-1.4, and the crystal morphology is columnar.
[0016] The application has the following advantages:
[0017] 1. The method for preparing anhydrite by phosphogypsum crystallization and purification provided by the application introduces a specific crystallization agent to regulate the growth process of anhydrite, so as to obtain anhydrite with high purity and high compressive strength. The above-mentioned method is suitable for preparing anhydrite from industrial by-product phosphogypsum with high phosphorus impurity content. The anhydrite produced has good crystallization conversion, excellent product quality, simple process, high efficiency, low energy consumption, and less water consumption compared with traditional methods, can utilize phosphogypsum waste, and realizes resource recycling.
[0018] 2、The method provided by the application can precisely control the morphology of anhydrite by regulating the growth environment of the anhydrite, so that columnar anhydrite crystals with a specific aspect ratio are prepared, and the application field of the anhydrite is effectively widened. BRIEF DESCRIPTION OF DRAWINGS
[0019] Figure 1 The SEM image of the anhydrite prepared in Example 1 of the application;
[0020] Figure 2 The SEM image of the anhydrite prepared in Comparative Example 1 of the application. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical scheme and advantages of the application clearer, the application will be described in detail below with reference to the drawings and specific examples.
[0022] Here, it should also be noted that, in order to avoid obscuring the application due to unnecessary details, only structures and / or processing steps closely related to the scheme of the application are shown in the drawings, and other details not closely related to the application are omitted.
[0023] In addition, it should also be noted that the term "comprise", "include" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements not explicitly listed or inherent to such a process, method, article or equipment.
[0024] In one aspect, the application provides a method for preparing anhydrite by phosphogypsum transformation and purification, comprising the following steps:
[0025] S1, uniformly mixing phosphogypsum, an acid mixture and a transformation agent to obtain a phosphogypsum mixed solution;
[0026] S2, reacting the phosphogypsum mixed solution obtained in step S1 at 80-100℃ for 100-150min, after the reaction is completed, washing at 90-100℃ until the supernatant is neutral, and then drying to obtain anhydrite.
[0027] In some embodiments, in step S1, the acid mixture is a mixture of sulfuric acid solution and nitric acid solution obtained by mixing in a volume ratio of (1-1.5):(2-2.6), the mass fraction of the sulfuric acid solution is 10-20%, the mass fraction of the nitric acid solution is 30-40%, the total phosphorus content of the phosphogypsum is less than 2.0%, and the total fluorine content is less than 1%.
[0028] In some embodiments, in step S1, the crystal transformation agent is composed of a di-alkali salt of ethylenediaminetetraacetic acid and an alkali metal chloride, the di-alkali salt of ethylenediaminetetraacetic acid is added in an amount of 0.3-0.5% of the dry basis mass of the phosphogypsum, and the alkali metal chloride is added in an amount of 0-15% of the dry basis mass of the phosphogypsum. Specifically, the di-alkali salt of ethylenediaminetetraacetic acid is at least one of disodium ethylenediaminetetraacetate and dipotassium ethylenediaminetetraacetate, and the alkali metal chloride is at least one of potassium chloride and sodium chloride.
[0029] In the above technical solution, by adding the crystal transformation agent with the above composition, the dehydration process of dihydrate gypsum can be controlled, and the selective adsorption of the di-alkali salt of ethylenediaminetetraacetic acid and the alkali metal chloride in the crystal transformation agent controls the growth of the (001) and (111) surfaces of dihydrate gypsum, and then the grown crystals are transformed from elongated fibers into short columns; at the same time, the crystal transformation agent can form a ring network "buffer film" composed of complexation of organic macromolecules and metal cations on the C-axis direction crystal surface of the crystal, which hinders the combination of the crystal unit on the C-axis (perpendicular to the (001), (111), (020), (400), and (200) directions) crystal surface, so that the growth rate of each crystal surface will remain in a balanced state, so that the short columnar dihydrate gypsum crystals are finally prepared.
[0030] In some embodiments, in step S1, the ratio of the mass (g) of the phosphogypsum, the mass (g) of the acid mixture, and the mass (g) of the crystal transformation agent is (0.8-1.2):(4.7-5.3):(1.6-2.2), where the mass of the phosphogypsum is measured based on the dry basis mass.
[0031] In some embodiments, in step S2, the drying treatment is performed at a temperature of 60-70℃ for 10-14h.
[0032] On the other hand, the present application provides an anhydrous gypsum, wherein the anhydrous gypsum has an aspect ratio of 0.9-1.4 and a columnar crystal morphology.
[0033] The method for preparing anhydrous gypsum by phosphogypsum crystal transformation and purification provided by the present application is further described below in conjunction with specific embodiments:
[0034] Embodiment 1
[0035] The present embodiment provides a method for preparing anhydrous gypsum by phosphogypsum crystal transformation and purification, which comprises the following steps:
[0036] S1, 10 g of phosphogypsum (dry), 50 g of acid mixture, 19 g of crystal modifier were mixed uniformly to obtain a phosphogypsum mixed solution; wherein the acid mixture was obtained by mixing 15 mL of a 16% sulfuric acid solution and 24 mL of a 34% nitric acid solution, and the crystal modifier was composed of 4 g of ethylenediaminetetraacetic acid disodium and 15 g of sodium chloride;
[0037] S2, the phosphogypsum mixed solution was heated at 95℃ for 120 min, after heating, hot filtration was performed, and the solid was washed with 100℃ water until the filtrate was neutral, then the solid was dried at 65±1℃ to constant weight to obtain anhydrous gypsum.
[0038] It should be noted that the phosphogypsum used in the embodiments of the present application is an industrial solid waste generated in the wet-process phosphoric acid production process, and the main component is CaSO4·2H2O, the total phosphorus content of the phosphogypsum is less than 2.0%, and the total fluorine content is less than 1%, and the remaining reagents and raw materials can be obtained by market purchase.
[0039] The SEM image of the anhydrous gypsum prepared in the present embodiment is shown in Figure 1 As can be seen from the figure, the anhydrous gypsum prepared under the condition is in short columnar shape, and the average length is 15 μm.
[0040] Examples 2 to 4
[0041] Examples 2 to 4 are different from Example 1 only in that the composition of the crystal modifier used in step S1 is different from that of Example 1, and the remaining experimental parameters and experimental conditions are the same as those of Example 1, which will not be described here.
[0042] According to the strength test method specified in GB / T 9776-2008 “Building Gypsum”, the performance of the anhydrous gypsum prepared in Examples 1 to 4 with different compositions of the crystal modifier and corresponding conditions was measured, and the test results are shown in Table 1. The results show that the optimal addition amount of ethylenediaminetetraacetic acid disodium and sodium chloride in the crystal modifier is 4 g and 15 g, because alkali metal salts and alkali metal chlorides will affect the growth of anhydrous calcium sulfate crystals on different surfaces. If the optimal dosage is not reached, not only the size of the crystal growth will not meet the expected size, but also etching marks will appear due to incomplete coverage of the crystal surface, thereby affecting the strength of the product. However, excessive addition of the crystal modifier will not greatly improve the strength of the product, because the crystal modifier plays a role by adsorbing the surface of the crystal, and excessive addition of the crystal modifier will only result in the crystal modifier being present in the solution and not being able to play a role.
[0043] Table 1 Comparison of the performance of the anhydrous gypsum prepared in Examples 1 to 4 with different compositions of the crystal modifier and corresponding conditions
[0044]
[0045]
[0046] Examples 5 to 7
[0047] Examples 5 to 7 differ from Example 1 only in that the source of the substances constituting the crystallization agent in Step S1 is different from Example 1, and the rest of the experimental parameters and experimental conditions are the same as Example 1, which will not be repeated here. The comparison of the properties of the anhydrous gypsum prepared under the corresponding conditions of the source of the crystallization agent of Example 1 and Examples 5 to 7 is shown in Table 2. Figure 2 As shown in Table 2, the results show that the mixed crystallization agent of ethylenediamine tetraacetic acid disodium salt in the multi-component organic acid salt and sodium chloride in the inorganic alkali metal salt is better for improving the performance of gypsum, because the two work together in the solution on several faces of the calcium sulfate crystal, and control the generation of short columnar anhydrous calcium sulfate crystals with good crystal form.
[0048] Table 2 Comparison of the properties of the anhydrous gypsum prepared under the corresponding conditions of the source of the crystallization agent of Example 1 and Examples 5 to 7
[0049]
[0050] Examples 8 to 10
[0051] Examples 8 to 10 differ from Example 1 only in that in Step S2, the reaction conditions are different from Example 1, and the rest of the experimental parameters and experimental conditions are the same as Example 1, which will not be repeated here. The comparison of the properties of the anhydrous gypsum prepared under the corresponding conditions of the reaction conditions of Example 1 and Examples 8 to 10 is shown in Table 3, and the results show that when the reaction time is less than 2h or the reaction temperature is lower than 95℃, the compressive strength cannot be improved, and when the reaction time is higher than 2h and the reaction temperature is higher than 95℃, the improvement of the compressive strength is not obvious, because the temperature is an important factor for changing the water activity of the solution, and the water activity of the solution directly affects the crystallization efficiency of the anhydrous calcium sulfate, and the crystallization needs time, but after a certain time, the ion balance is reached, and the crystallization rate no longer changes significantly.
[0052] Table 3 Comparison of the properties of the anhydrous gypsum prepared under the corresponding conditions of the reaction conditions of Example 1 and Examples 8 to 10
[0053]
[0054] Comparative Example 1
[0055] Comparative Example 1 differs from Example 1 only in that only ethylenediamine tetraacetic acid disodium salt is used as the crystallization agent, and the amount of ethylenediamine tetraacetic acid disodium salt added in Comparative Example 1 is equal to the sum of the mass of ethylenediamine tetraacetic acid disodium salt and sodium chloride in Example 1, and the rest of the experimental parameters and experimental conditions are the same as Example 1, which will not be repeated here. The SEM image of the product obtained in this comparative example is shown in Figure 2. Figure 1As shown in the figure, the anhydrous gypsum prepared under the condition is needle-shaped, and the average length thereof is 200 μm.
[0056] Comparative Example 2
[0057] Comparative Example 2 and Example 1 differ only in that sodium chloride is used as the crystal modifier alone, and the amount of sodium chloride added in Comparative Example 1 is equal to the sum of the amounts of ethylenediaminetetraacetic acid disodium and sodium chloride in Example 1, and the rest of the experimental parameters and experimental conditions are the same as those in Example 1, which will not be repeated here.
[0058] The performance comparison of the anhydrous gypsum prepared in Example 1 and Comparative Examples 1 to 2 is shown in Table 4, and the results show that the addition of ethylenediaminetetraacetic acid disodium or sodium chloride alone does not significantly improve the strength of the product, because the use of one substance alone as a crystal modifier can only affect the growth of some faces of the crystal, and if the effects are not coordinated, the crystal will grow excessively along the undesirable axis, resulting in an undesirable crystal form, and the strength will not be as good as that of the short columnar crystal.
[0059] Table 4 Performance comparison of the anhydrous gypsum prepared in Example 1 and Comparative Examples 1 to 2
[0060]
[0061] The above examples are only used to illustrate the technical solutions of the present application, but not limit the present application. Although the present application has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present application can be modified or replaced by equivalents without departing from the spirit and scope of the present application.
Claims
1. A method for preparing anhydrite by phosphogypsum recrystallization purification, characterized by, The method comprises the following steps: S1, uniformly mixing phosphogypsum, an acid mixture, and a crystal modifier to obtain a phosphogypsum mixed solution; the acid mixture is composed of a nitric acid solution and a sulfuric acid solution; S2, reacting the phosphogypsum mixed solution obtained in step S1 at 80-100℃ for 100-150 min, and then drying to obtain anhydrous gypsum.
2. The method of claim 1, wherein, In step S1, the crystal modifier is composed of a di-alkali metal salt of ethylenediaminetetraacetic acid and an alkali metal chloride, the di-alkali metal salt of ethylenediaminetetraacetic acid is added in an amount of 0.3-0.5% of the dry basis mass of the phosphogypsum, and the alkali metal chloride is added in an amount of 0-15% of the dry basis mass of the phosphogypsum.
3. The method of claim 2, wherein, The di-alkali metal salt of ethylenediaminetetraacetic acid is disodium ethylenediaminetetraacetate and / or dipotassium ethylenediaminetetraacetate, and the alkali metal chloride is potassium chloride and / or sodium chloride.
4. The method of claim 1, wherein, In step S1, the ratio of the dry basis mass of the phosphogypsum, the volume of the acid mixture, and the mass of the crystal modifier is (0.8-1.2):(4.7-5.3):(1.6-2.2).
5. The method of claim 1, wherein, In step S1, the mass fraction of the nitric acid solution is 30-40%, the mass fraction of the sulfuric acid solution is 10-20%, and the volume ratio of the sulfuric acid solution to the nitric acid solution is (1-1.5):(2-2.6).
6. The method of claim 1, wherein, In step S2, the drying temperature is 60-70℃, and the drying time is 10-14 h.
7. Anhydrous gypsum, characterized in that, The anhydrous gypsum is prepared by the method of any one of claims 1-6.
8. The anhydrous gypsum according to claim 7, characterized in that, The anhydrous gypsum has an aspect ratio of 0.9-1.4 and a columnar crystal morphology.